1999
DOI: 10.1590/s0041-87811999000100005
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study with a glutamine-supplemented enteral formula in critically ill infants

Abstract: Seriously ill infants often display protein-calorie malnutrition due to the metabolic demands of sepsis and respiratory failure. Glutamine has been classified as a conditionally essential amino acid, with special usefulness in critical patients. Immunomodulation, gut protection, and prevention of protein depletion are mentioned among its positive effects in such circumstances. With the intent of evaluating the tolerance and clinical impact of a glutamine supplement in seriously ill infants, a prospective rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 5 publications
0
16
0
3
Order By: Relevance
“…Overall, this study results showed that glutamine supplementation was safe, but had no effect on duration of TPN, tolerance of enteral feeds, or intestinal absorption or barrier function. However, in a PRCT pilot study Barbosa and colleagues [150] examined the tolerance and efficiency of glutamine in a pediatric intensive care unit setting with nine mechanically ventilated infants (treatment group = 5, and control group = 4). Their results showed that tolerance to glutamine-supplemented diet was good.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this study results showed that glutamine supplementation was safe, but had no effect on duration of TPN, tolerance of enteral feeds, or intestinal absorption or barrier function. However, in a PRCT pilot study Barbosa and colleagues [150] examined the tolerance and efficiency of glutamine in a pediatric intensive care unit setting with nine mechanically ventilated infants (treatment group = 5, and control group = 4). Their results showed that tolerance to glutamine-supplemented diet was good.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação aos lactentes e às crianças maiores, não há trabalhos, até o momento, que demonstrem benefícios da glutamina em promover melhor tolerância à dieta enteral 9,10 . O assunto também continua controverso em relação aos adultos, visto que os estudos, até o momento com pacientes pós-transplante de medula óssea e aqueles criticamente enfermos, demonstram RN= recém-nascidos; NP= nutrição parenteral; TGI= trato gastrintestinal; EV= endovenoso; AA= aminoácidos; SOG= sonda orogástrica; IG= idade gestacional; CRIB= escore clínico de risco para recém-nascidos.…”
Section: Exclusão Durante Estudounclassified
“…Na presente revisão, verificou-se que a redução de infecção foi significante somente nos estudos de Dallas et al 11 e Neu et al 13 , enquanto que no grupo estudado por Barbosa et al 10 , foi evidenciada apenas uma tendência à redução -fato decorrente, provavelmente, da pequena amostra de pacientes. Nenhuma diferença foi observada nos estudos de Anderson et al 9 , Lacey et al 12 14 , a suplementação deste aminoácido não promoveu redução da mortalidade.…”
Section: Exclusão Durante Estudounclassified
See 1 more Smart Citation
“…They are believed to play an active role in enhancing immunity and help wound healing. Trials on immunonutrition have shown beneficial results [25].…”
Section: Assessment Of Nutritional Statusmentioning
confidence: 99%